Political Bargaining, Religious Economy, and Constitutional Policy Outcomes: The Case of Santiago del Estero, Argentina (1939) - Tenti, María Mercedes (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the dynamics of political bargaining and the application of religious economy logic in shaping constitutional policy outcomes in Santiago del Estero, Argentina, during the 1939 Constituent Convention. The research aims to understand how local political configurations enabled the maintenance of secular education in the provincial constitution despite strong institutional support for religious education from the Catholic Church, which was backed by ecclesiastical networks, Catholic media, and executive political maneuvers. Using a qualitative historical approach, the study analyzes archival sources, including official session minutes, debate transcripts, and attendance records of convention members. The findings reveal that the Catholic Church engaged in strategic issue trading—exchanging concessions on moral policies such as education for gains on other agendas like gambling prohibition—while local secular coalitions of teachers, intellectuals, cross-party politicians, and segments of the Catholic elite successfully defended the principle of educational neutrality. These results contribute to the literature on religion and politics in Latin America by highlighting how provincial-level dynamics can diverge from national trends when supported by effective coalition-building, public mobilization, and pragmatic negotiation strategies. The study’s implications suggest that while such bargaining can produce balanced policy outcomes, it also risks fostering moral relativism and eroding institutional credibility when values are subordinated to short-term political gains. The originality of this research lies in its focus on a subnational case that challenges the predominant national pattern in Argentina’s religious-political relations, offering a nuanced analytical framework for understanding adaptive and pragmatic interactions between religion and politics in localized contexts.